Insufficiency Fractures vs. Low-Energy Pelvic Ring Fractures – Epidemiological, Diagnostic and Therapeutic Characteristics of Fragility Fractures of the Pelvic Ring - Sterneder, Manuel; Lang, Patricia; Riesner, Hans-Joachim; Hackenbroch, Carsten; Friemert, Benedikt; Palm, Hans-Georg (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background Fragility fractures of the pelvis (FFP) encompass two fracture entities: fracture after low-energy trauma and insufficiency fracture without trauma. It is unclear whether the two subgroups differ in terms of diagnosis and therapy. The aim of this retrospective study was to evaluate insufficiency fractures with regard to defined parameters and to compare specific parameters with the fractures after low-energy trauma.Patients and Methods In the period from 2008 to 2017, 203 patients with FFP were recorded at our clinic (Level 1 Trauma Centre DGU, SAV approval). Of these, 25 had an insufficiency fracture and 178 had a pelvic ring fracture after low-energy trauma. Epidemiological, diagnostic and therapeutic parameters were examined.Results There was a relative increase in the insufficiency fracture within the FFP (2008 – 2009: 5.0% vs. 2015 – 2017: 17.8%). In these patients, osteoporosis tended to be more pronounced than in patients after low-energy trauma (t-value: − 3.66 vs. − 3.13). The diagnosis of insufficiency fractures showed increased use of MRI and DECT (60.9% vs. 26.0%) and a high proportion of type IV fractures after FFP (40.0% vs. 7.9%). In terms of therapy, surgical treatment of the insufficiency fracture was sought more often (68,2% vs. 52,1%), with a tendency towards increased use of combined osteosynthesis procedures (14.3% vs. 7.6%).Conclusion We were able to show that as the number of cases increases, the insufficiency fracture becomes more important within FFP. If these patients tend to have more pronounced osteoporosis, particular attention should be paid to the diagnosis and adequate therapy of the osteoporosis, especially in the case of an insufficiency fracture. In addition to the increased diagnostic testing using MRI and DECT to detect oedema and the increased surgical therapy for this type of fracture, it is also noteworthy that the insufficiency fracture can cause higher-grade fractures after FFP.Hintergrund Innerhalb der Fragilitätsfrakturen des Beckens (Fragility Fractures of the Pelvis, FFP) existieren mit der Fraktur nach niedrigenergetischem Trauma und der Insuffizienzfraktur ohne Trauma 2 Frakturentitäten. Unklar ist, ob sich beide Subgruppen bez. Diagnostik und Therapie differenzieren. Ziel dieser retrospektiven Studie war es, die Insuffizienzfrakturen hinsichtlich definierter Parameter zu evaluieren und spezifische Parameter mit den Frakturen nach niedrigenergetischem Trauma zu vergleichen.Patienten und Methoden Im Zeitraum von 2008 bis 2017 waren an unserer Klinik (überregionales TraumaZentrum DGU, SAV-Zulassung) 203 Patienten mit FFP zu verzeichnen. Davon hatten 25 eine Insuffizienzfraktur und 178 eine Beckenringfraktur nach niedrigenergetischem Trauma. Beleuchtet wurden epidemiologische, diagnostische und therapeutische Parameter.Ergebnisse Es zeigte sich eine relative Zunahme der Insuffizienzfraktur innerhalb der FFP (2008 – 2009: 5,0% vs. 2015 – 2017: 17,8%). Bei diesen Patienten war tendenziell eine ausgeprägtere Osteoporose im Vergleich zu Patienten nach niedrigenergetischem Trauma (t-Wert: − 3,66 vs. − 3,13) festzustellen. Diagnostisch zeigte sich bei Insuffizienzfrakturen ein vermehrter Einsatz von MRT und DECT (60,9 vs. 26,0%) und ein hoher Anteil an Typ-IV-Frakturen nach FFP (40,0 vs. 7,9%). Therapeutisch wurde häufiger eine operative Versorgung der Insuffizienzfraktur angestrebt (68,2 vs. 52,1%) mit tendenziell vermehrtem Einsatz kombinierter Osteosyntheseverfahren (14,3 vs. 7,6%).Schlussfolgerung Wir konnten zeigen, dass bei steigenden Fallzahlen die Insuffizienzfraktur innerhalb der FFP an Bedeutung gewinnt. Bei einer tendenziell ausgeprägteren Osteoporose dieser Patienten sollte insbesondere bei der Insuffizienzfraktur das Augenmerk auf die Diagnostik und adäquate Therapie der Osteoporose gelegt werden. Bemerkenswert ist neben der vermehrten Diagnostik mittels MRT und DECT zum Ödemnachweis und der vermehrten operativen Therapie bei dieser Frakturentität aber auch, dass die Insuffizienzfraktur höhere Frakturschweregrade nach FFP hervorrufen kann.
Keywords: fragility fracture; pelvic fracture; insufficiency fracture; DECT; MRI